Utility of Magnetic Resonance Imaging for Predicting Severity of Sciatic Nerve Injury. Issue 4 (July 2018) - Ahlawat, Shivani; Belzberg, Allan J.; Fayad, Laura M.
Abstract : Objective: This study aimed to investigate the diagnostic accuracy of magnetic resonance (MR) imaging for categorizing sciatic peripheral nerve injury (PNI) as high-grade (Sunderland grades IV–V) or low-grade (Sunderland grades I–III) PNI. Methods: In this institutional review board–approved, Health Insurance Portability and Accountability Act–compliant retrospective study, consecutive MR imaging of the pelvis and thighs, performed for the evaluation of traumatic sciatic neuropathy, was reviewed for sciatic nerve signal intensity, size, architectural distortion, bulbous enlargement, perineural fibrosis, discontinuity, and muscle denervation changes. Clinical data, electrodiagnostic testing, and surgical history were used to determine PNI grade (high, low). Descriptive and diagnostic performance statistics were applied. Results: Of 24 patients, there were 12 high-grade and 12 low-grade PNI. There was no significant difference in signal intensity or size between high-grade and low-grade PNI (1.3 ± 0.5 cm vs 0.9 ± 0.3 cm, P = 0.09). The sensitivity and specificity for the presence of individual features in predicting high-grade injury were 83% and 67% for architectural distortion, 58% and 75% for bulbous enlargement, 50% and 83% for perineural fibrosis, 25% and 100% for discontinuity, and 67% and 75% for skeletal muscle denervation changes, respectively. Overall, the sensitivity and specificity of MR imaging for categorizing sciatic PNI as high grade was 75% and 83%, respectively. Conclusions: The MR characterization of PNI severity remains challenging. Useful features indicative of high-grade PNI include bulbous enlargement, perineural fibrosis, muscle denervation changes, and nerve discontinuity.